Factors Influencing Cooperative Membership and Share Increment: An Application of the Logistic Regression Analysis in the Malaysian Cooperatives - Azmah, Othman; Fatimah, Kari; Rohana, Jani; Rosita, Hamdan (Billion Brains, 2012)
This study investigates factors that influence cooperative membership and their share capital increment using the binary logistic regression analysis. Data from a survey conducted in late 2008 with 380 respondents (members and non-members) from cooperatives in Selangor and Kuala Lumpur were used to investigate the factors. The study showed that age, occupation, AGM attendance and membership duration are important predictors in the model. It was found that people in the older age group (45 years thru highest) are 19 times more likely to become members. Those in the private sector are 0.517 less likely to become members as compared to government servant. Those that diligently attended cooperative AGM were found to be 4 times more likely to increase their cooperative share holding. Field of Research: Cooperative, Development economics